Analysis of β-casein variants in Gir and crossbreed cows from Mumbai farms by Reverse phase high pressure liquid chromatography. - Veeraja Loken et al. (Indian Journal of Dairy Science, 2025)
Beta casein polymorphism and its association with health implications on human health have attained crucial attention worldwide.  In India, with the increasing population of exotic and crossbred cows, which produce milk containing A1 and B β-casein types, it is essential to screen the cows and bulls for their beta casein variant to avoid the health implications attributed to A1 and B β-casein cow milk. There are no available reports of milk protein analysis by HPLC method for beta casein variants from India. We have analysed 86 milk samples from Pure Gir (n=49), crossbred Holstein Frisian (n=19), crossbred Jersey (n=14) and crossbred Gir (n=4) cows by high-pressure liquid chromatography (HPLC) using a Photodiode array detector (PDA)  to analyse A1 and A2 beta-casein proteins in milk samples. HPLC peaks for A1 and A2 β-casein in HPLC chromatogram were identified using milk samples of selected cows whose β-casein variant was conformed using Polymerase Chain reaction. All milk samples from pure Gir cows were shown A2 whereas a maximum number of crossbred Holstein Frisian and crossbred Jersey milk samples showed two peaks of A1 and A2.